Utilisation of autopsy services for posthumous monetary compensation among black mine workers in South Africa - Banyini, Audrey Vukosi (My University, 2013)
Background: In the South African mining sector, cardiorespiratory autopsy examinations are conducted on deceased mineworkers to determine eligibility for compensation, irrespective of the cause of death. An autopsy examination is a right under the Occupational Diseases in Mines and Works Act, Act No. 78 of 1973 (ODMWA) except for mineworkers who received maximum compensation awarded for occupational lung diseases in second degree category during life. Compensation awards to the deceased mineworkers’ dependants can contribute to short- or medium-term poverty alleviation. In spite of the possible benefits, ODMWA autopsy utilisation by black mineworkers’ families is incomplete. Increased utilisation has the potential to assist in alleviating poverty. It is imperative to understand what contributes to autopsy utilisation or non-utilisation by black mineworkers, as this will guide public health policy intervention regarding ODMWA autopsy. Aims: The study set out to quantify the monetary contribution of ODMWA autopsy to mineworkers’ families, to estimate the loss of potential financial benefits due to autopsy non-utilisation; define the characteristics of those deceased mineworkers who did not use the autopsy service (to tentatively formulate reasons for not using autopsy); and to describe the barriers and enablers that contribute to ODMWA autopsy utilisation. Methods: The study was primarily qualitative; however quantitave investigations were undertaken using data from the National Institute for Occupational Health (NIOH), the Medical Bureau for Occupational Diseases (MBOD), and The Employment Bureau of Africa (TEBA). First, a descriptive study was undertaken to determine autopsy utilisation and establish the amount of compensation paid to dependants of deceased mineworkers over a ten-year period (2001- 2010) following autopsy examination; and to estimate the loss of financial benefits from autopsy non-utilisation. Also, the characteristics of those deceased ii mineworkers recorded by MBOD in 2001-2008 but who did not undergo autopsy examination were investigated using data in the subjects’ MBOD files. The characteristics investigated included previous submissions to MBOD or date of last submission; age of the deceased at death and place and date of death; labour history, the last date of work; cause of death and medical information. Second, in-depth interviews on perceptions of autopsy were carried out with participants. The key participants were former and in-service mineworkers, relatives and widows of deceased mineworkers and others (traditional healers, occupational health practitioners, community and organised labour leaders). These categories of participants were selected because of the particular perspective that they were likely to bring to the study. A semistructured questionnaire was used to guide the in-depth interviews. All interview data were transcribed into English. Key ideas generated were noted at the end of each interview. The notes were examined for overall depth and meaning. The notes for each respondent were uploaded in their groups onto 2003 MAXqda PC (2003) and coded into segments and grouped into categories. Emerging themes were identified using a conceptual framework and meaning interpreted. Results Autopsy utilisation: 71% of in-service mineworkers over the 10-year period were employed by mines affiliated with TEBA. Using the annual TEBA-reported deaths as the denominator and ODMWA autopsies as the numerator, it was estimated that during 2000-2010, autopsy utilisation by black miners who died in service ranged from 30-46%. It is argued that these figures were an over-estimate as they did not include former mineworkers or in-service mineworkers working for TEBA non-affiliated mines. The results suggest that the majority of autopsy examinations were of TEBA registered mineworkers. Following autopsy examinations over ten years, 311 deceased mineworkers not compensated in life were certified by MBOD to suffer occupational lung disease in the first degree and 2 426 in the second degree categories respectively following autopsy examination. Autopsy non-utilisation: From the TEBA recorded deaths and ODMWA autopsies performed by NIOH, there were 15 064 mineworkers who did not undergo autopsy examination during 2001-2012. It is estimated that 355 mineworkers would have been certified in the first degree category, and 2 769 in the second degree category had they come to autopsy. Contribution of ODMWA autopsy to compensation: Each family of the 311 deceased mineworkers certified with occupational lung disease in the first degree category would have received an average lump sum payment of $8 750. Similarly each family of the 2 426 mineworkers certified with occupational lung disease in the second degree category would have received an average lump sum payment of $12 907 Additionally, each family of the 59 cases upgraded from first to second degree category following autopsy examination would have received an average lump sum payment of $5 250. If assumptions were made that Stewart (2007)’s findings on financial spending on basic needs such as food person per family of seven members were similar to that of mineworkers compensated following ODMWA autopsy; households that received $8 750 in compensation would have had sufficient money to buy food for 29-47 months. Similarly those who received $12 907.79 and $5 250 could have managed to buy food for 49-80 and 20-33 months respectively. Characteristics of deceased mineworkers: Tentative reasons of no autopsy examination were dying at home, recent MBOD submission, age of the mineworker, previous and current TB infection certified by MBOD. Ninety six percent of them died at home and four percent died in district public hospitals. Sixty four percent were recently submitted to MBOD and of these mineworkers, 70% had pulmonary tuberculosis. The majority were fairly young i.e. 52% died before the age of 50 years and a further 12% before the age of 60 years. Barriers and enablers of ODMWA autopsy: Barriers and enablers of ODMWA autopsy consent and utilisation were found to be diverse, complex, and multifaceted such that a multipronged intervention strategy would be required to increase utilisation. The barriers and enablers of ODMWA autopsy were in individual/family; socio-cultural and institutional perspectives. The respondents could rationalise their acceptance or rejection of autopsy within their own individual cultural or religious belief system and these varied according to the individual’s experiences, family beliefs and societal practices. Enablers regarding consent to ODMWA autopsy were dissociation of the body from the soul, matrilineal relations to the deceased mineworker, communication with ancestors while the mineworker was healthy, deaths described as bad by participants. Key to autopsy consent facilitation was the mineworkers communicating their acceptance of ODMWA autopsy examination to their families and by communicating this intention to their ancestors -where this was consistent with their belief system. Foremost among the barriers to ODMWA autopsy utilisation was the requirement of formal consent within a biomedical framework, which clashed with certain socio-cultural beliefs. These cultural barriers were associated with patriarchal relations to the deceased mineworkers, beliefs that being buried without cardiorespiratory organs was synonymous to burying an empty box, health workers’ attitudes, mistrust, commodification of body parts, community traditional norms and practices and unequal power relations on decision making which led to exclusion of potential beneficiaries (widows and children). Conclusion: The study documented that a large number of in-service black mineworkers did not utilise ODMWA autopsy in spite of the potential financial benefits demonstrated. Additionally, former mineworkers who did not utilise autopsy were under fifty years of age, died of PTB within twelve months of leaving mines at their homes. The study found cultural beliefs that were barriers to autopsy utilisation, but also those that may enable these barriers to be overcome. The finding that the cultural beliefs were not static or uniform suggested that increasing autopsy consent would require comprehensive communication and awareness intervention strategies aimed at individual, family and community levels. The intervention strategies should not be once-off, but long-term and should address the cultural beliefs. The enablers of autopsy utilisation could be used in the awareness messages. Further research is required to investigate the attitude of health care providers (nurses, traditional healers, medical practitioners etc) to ODMWA autopsy utilisation, investigate the process of decentralising the autopsy examination and the impact this will have on appeals, standardisation and resources; and to examine the legal framework which would make ODMWA autopsy permissible without the current consent requirements, possibly under similar conditions to forensic medicine. Revising consent requirements is important to alleviate the conflict felt by spouses, mineworkers and relatives who have to satisfy cultural imperatives which are at odds with giving consent to permanent removal of cardiorespiratory organs. ODMWA should remain in place until exposures resulting in occupational lung diseases have been reduced to non-disease-causing levels or no new occupational diseases are found at autopsy. The enablers and barriers to ODMWA autopsy found in this study may be generalisable to similar socio-cultural environments outside South Africa.
Keywords: Forensic Medicine; Autopsy